Perancangan UI/UX Aplikasi Crowdfunding Syariah Untuk UMKM Menggunakan Metode User-Centered Design - Thea Anugrah Felicia; Rahmat Fauzi; Faishal Mufied Al Anshary (STMIK Budi Darma, 2023)
The Indonesian economy is influenced by Micro, Small, and Medium Enterprises (MSMEs). Even though MSMEs are an important part of the Indonesian economy, they still need help developing their business, including capital problems. Of the total MSMEs, 17.5% can only get capital loans through banks, and 82.5% access capital from non-banks. Another problem MSMEs face is that their income still needs to be improved. Hence, they sometimes need help to make interest payments or repay the principal on loans. In addition, MSME actors need more assets for collateral when they want to make loans. Thus, it is necessary to develop a website-based crowdfunding application that can provide easy access to funding so that MSME actors can easily obtain capital and help develop the Islamic finance industry. The design of this website uses the user-centered design method. It has been tested with three iterations using maze tools with the first parameter value, namely the Usability Score (MAUS) with a value of 68, and the second parameter, namely the System Usability Scale (SUS) with a value of 67.67 with a Marginal acceptability range. In the second iteration, the Maze Usability Score (MAUS) is 79, and the System Usability Scale (SUS) is 74.25 with the Acceptability range Acceptable. Then, in the last iteration, the Maze Usability Score (MAUS) was 84, and the System Usability Scale (SUS) was 80.25 with the Acceptability range Acceptable. So with the results of these three iterations, the Tasha Sharia Crowdfunding website can meet user needs